2018
DOI: 10.3390/s18092743
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Classification of Gait Impairments Using a Markerless 2D Video-Based System

Abstract: Systemic disorders affecting an individual can cause gait impairments. Successful acquisition and evaluation of features representing such impairments make it possible to estimate the severity of those disorders, which is important information for monitoring patients’ health evolution. However, current state-of-the-art systems perform the acquisition and evaluation of these features in specially equipped laboratories, typically limiting the periodicity of evaluations. With the objective of making health monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 37 publications
0
56
0
Order By: Relevance
“…The other two datasets, however, are captured in less constrained environments, where the segmentation of silhouettes is far form perfect, often missing parts of the walking person's silhouette. Thus, it can be concluded that the proposed finetuning scheme generalizes well across datasets, even in the presence of silhouette segmentation errors, which affect the performance of most systems based on biomechanical handcrafted features [1]. Table III also reports results for the state-of-the-art methods.…”
Section: B Classification Of Gait Pathologiesmentioning
confidence: 85%
See 4 more Smart Citations
“…The other two datasets, however, are captured in less constrained environments, where the segmentation of silhouettes is far form perfect, often missing parts of the walking person's silhouette. Thus, it can be concluded that the proposed finetuning scheme generalizes well across datasets, even in the presence of silhouette segmentation errors, which affect the performance of most systems based on biomechanical handcrafted features [1]. Table III also reports results for the state-of-the-art methods.…”
Section: B Classification Of Gait Pathologiesmentioning
confidence: 85%
“…Most vision based systems that rely on a 2D video only perform a binary classification of whether the observed gait is normal or impaired. While some systems, such as [1], can identify gait pathologies, their results are very much dependent on the quality of the silhouettes used. In such situations, poor silhouette segmentation can significantly reduce the classification results.…”
Section: B Motivation and Contributionmentioning
confidence: 99%
See 3 more Smart Citations